How to implant left bundle branch pacing lead in routine clinical practice. (26th September 2019) - Chen, Keping; Li, Yuqiu
Abstract: Introduction: Left bundle branch pacing (LBBP) is characterized with a low and stable pacing capture threshold, relatively narrow QRS duration due to fast left ventricular activation, and direct excitation of the diseased left bundle branch. This report aims to describe the methods, procedural skills, and clinical implications of performing LBBP implantation. Methods and Results: LBBP is achieved by transventricular‐septal approach. There are two methods to identify the location for LBBP lead placement: the single‐lead method and the dual‐lead method. During implantation, the unique transition of the paced QRS morphology and pacing parameter changes are important for guiding the lead ‐ advancement to the left side of the interventricular septum. In our experience, LBBP can be safely performed in most patients requiring pacemaker therapy. Conclusion: Clinical development of LBBP is at an early but encouraging phase with increasing clinical use, and a standardized procedure with improved delivery tools and pacing leads is needed, as well as long‐term efficacy and safety.